Time course of flow-mediated dilation and vascular endothelial growth factor following acute stroke - Billinger, Sandra A (J Stroke Cerebrovasc Dis, 2017)
OBJECTIVES: People after stroke demonstrate alterations in vascular endothelial function measured by flow-mediated dilation. Limited information is available in the literature to possible protective factors following stroke. The aims of the secondary analysis were: 1) characterize the time course of vascular endothelial function using flow-mediated dilation at 72 hours post-stroke and one week later during inpatient stroke rehabilitation and 2) whether flow-mediated dilation was related to vascular endothelial growth factor, brain-derived neurotrophic factor or estimated pre-stroke peak oxygen uptake. METHODS: Flow-mediated dilation using Doppler ultrasound was assessed in bilateral brachial arteries at the defined time points. Flow-mediated dilation and blood draws occurred on the same day between 7:30 am and 9:00 am following an overnight fast. ELISA was used to quantify plasma vascular endothelial growth factor and brain-derived neurotrophic factor values. A non-exercise estimate was used to calculate pre-stroke peak oxygen uptake. RESULTS: We have shown that between limb differences are evident within 72 hours post-stroke and remain one week later during inpatient rehabilitation. Higher values for vascular endothelial growth factor were associated with increased flow-mediated dilation at both time points. Higher estimated pre-stroke peak oxygen uptake was related to flow-mediated dilation. Brain-derived neurotrophic factor was not related to any outcome measures. CONCLUSIONS: Unique vascular adaptations start early after stroke in the stroke-affected limb and remain through inpatient stroke rehabilitation. Vascular endothelial growth factor and pre-stroke physical activity may have a protective role in vascular function following stroke. Future work should focus on mechanistic pathways for preservation of vascular health.